Hubungan Penggunaan Gadget Dengan Interaksi Sosial Anak Usia (3-5 Tahun) - Asrina Pitayanti; Kuswanto Kuswanto; Nashrul Wahyu Suryawan (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
The use of gadgets in children requires important attention for all parents because it influences the disruption of children's social interaction patterns, gadgets become a strong thing in children's memories. They use gadgets to watch YouTube, games, TikTok, listen to children's songs, cartoons, etc. When using gadgets, children tend to be engrossed in themselves, ignoring their surroundings, which has an impact at school, children prefer to play alone, when they try to call or talk to them, these children tend to remain silent, don't answer, don't look at the person they are talking to, children tend to be shy. , not confident. The aim of this research was to determine the relationship between gadget use and social interaction in children aged 3-5 years. The research design that will be used to identify the relationship between gadget use and children's social interactions is an observational analytical design using a cross-sectional approach. The independent variable or what is called independent from this research is the use of gadgets in PAUD age children, while the dependent variable or what is usually called dependent from this research is the social interaction of children aged (3-5 years). The sample for this research is: In this study, the sample used was as many as respondents from all children aged (3-5 years) in PAUD Kuwiran Village, Kare District, Madiun Regency, totaling 42 children/students. The sampling technique in this study used the Simple Random Sampling research technique. The research instrument used is a closed questionnaire which will be given to the respondent's parents. The use of gadgets among children aged (3-5 years) is high for 26 children (68.4%). Social Interaction in Children Aged (3-5 Years) is moderate for 25 children (65.8%). There is a significant relationship of -0.362 which is categorized as sufficient (0.26-0.599) between the use of gadgets and the social interaction of children aged (3-5 years) in PAUD. Providing positive guidance and direction regarding the use of gadgets so that children's interactions with the surrounding environment are not disturbed, children can build social interaction relationships.